Fikih Pancasila (Reinterpretasi Patriotisme dalam Upaya Meneguhkan Keutuhan NKRI) - Miftahul ulum (STAI Syaichona Moh. Cholil Bangkalan, 2019)
Mahfud MD states that the Pancasila State is a constitutional state and is final, even in terms of religious/fiqh law can be declared valid and correct. The results of the ijtihad of the ulama of ushul fiqh also mentioned that the choice of national law based on the Pancasila and the 1945 Constitution of the Republic of Indonesia was the right choice and was recognized syara'. Indonesia's legal state also accepts the spiritual value of religious law. Written law and all procedural provisions (rechtsstaaf) are accepted but must be put in order to uphold justice (the rule of law). Written provisions that prevent justice can be abandoned. This is confirmed in the provisions of Article 24 paragraph (1) of the 1945 Constitution which states that the function of the judicial authority is to enforce law and justice, and Article 28D paragraph (1) concerning the right to obtain legal certainty and Article 28H that the law must be built on the basis of justice benefits. Jurisprudence law with national law has the same substance in maintaining and encouraging the development of a legal system based on social justice and public benefit (al-manfa'ah al-ammah) as has also been voiced and championed by the founders of the state when they are compiling the state ideology, namely Pancasila. Those who are predominantly Muslim have an open attitude to respect and accommodate the interests of other faith groups and religions. Abdurrahman Wahid also emphasized that the founders of the nation (such as Ki Bagus Hadikusumo, Abdul Wahid Hasyim, Kahar Mudzakkar, Agus Salim, and Ahmad Subardjo) who were experts in the field of Jurisprudence had absorbed and adopted the principles and objectives of fiqh law that had a value of justice, benefit, humanity and shura in the Pancasila state system.